The Practice of Gambling (Maisir) in Various Forms of Modern Economic Activity - Mardiah, Mardiah (Lafadz Jaya Publisher, 2025)
The word Maisir in Arabic literally means to obtain something very easily without hard work or to gain profit without working. It is anything that involves gambling, betting or risky games. Another term used in the Quran is the word `azlam' which means the practice of gambling. Economic activity plays a vital role in creating a prosperous, just and prosperous society. Islam teaches in the economic system of its ummah, based on the values of justice that must be upheld, and become the main principle for conducting economic activities. Every economic activity must contain elements of benefit and not mistreatment of himself and others, so that economic activity can create community welfare equally. Conducting economic activities is not allowed to be done if it contains elements of gharar, maysir and usury or taking the rights of others by false means. In the Qur'an letter al-Baqarah: 219 and surat al- Ma'idah: 90 and 91, it is known that gambling is an abominable act that is forbidden by Islam. The scholars also said that gambling (maisir) is a game where the winner gets a certain amount of money or goods without reasonable effort and can make people fall into the valley of poverty because it contains three elements, namely games/competitions, there is a bet, luck. Today's modern conventional (non-sharia) businesses generally contain three elements that are prohibited in Islamic economic ideology, namely gharar, maisir and riba. This happens not separated from the reality of conventional business development trends and not widespread awareness and coverage of economic services based on Islamic economics. Bank Muamalat Indonesia (BMI) is the first purely Islamic bank in Indonesia which in principle all of its main products both in the service of Financing Strategy products (deposits funds) and financing products (financing) based on the Islamic system (profit sharing). BMI seeks to implement aspects of Islamic economic ideology that consistently avoids gharar, maisir and usury.